Painful lives: Understanding self-harm amongst care-experienced women in prison - Fitzpatrick, Claire (Criminology & criminal justice, 2023)
Self-harm incidents in custody in England and Wales recently reached a record high, increasing particularly in women’s establishments. This article explores experiences of self-harm by drawing on interviews with care-experienced women in prison in England. Using prior care experience as the underlying thread enables us to explore this topic through a different lens. Considering the functions of self-harm that women described, including the communication, alleviation and ending of pain, highlights the painful lives of those experiencing both state care and control institutions. This reveals that women have often been failed across different systems, sometimes with devastating consequences. Urgent attention must be paid to the system failures affecting those previously deemed by the state to require welfare and protection.